Intervensi Berbasis Keluarga pada Anak dengan Stunting - Aziz Nashiruddin Habibie; Ferry Efendi; Eka Misbahatul M Has (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effectiveness of family-based interventions for children with stunting. The method used is a systematic review of family-based interventions for children with stunting. The results showed that family-based interventions in the form of health counseling through the family and family empowerment in providing nutrition affected the nutritional status of stunted children. Family-based interventions through family empowerment can improve the nutritional status of stunted children. In conclusion, family-based interventions effectively improve the nutritional status of stunted children. Keywords: Family, Prevention, Stunting, Nutrition Therapy